Reversible video watermarking through recursive histogram modification - VURAL, CABİR (SPRINGER, 2017)
In this study, a new reversible video watermarking method is developed. Unlike the existing reversible video watermarking algorithms that are based on motion compensated prediction or interpolation error expansion, motion compensated interpolation errors in the proposed method are watermarked in a totally different manner with the aid of recursive histogram modification algorithm developed recently for the purpose of reversible image watermarking. However, the recursive histogram modification can not be used directly for reversible video watermarking since the important problems of ensuring reversibility for each frame and distribution of total capacity among frames are encountered. In this study, novel ideas are proposed to solve the aforementioned two problems. The proposed method is tested on the video sequences commonly used in the literature. It is shown to give better performance than the existing reversible video watermarking algorithms in terms of capacity and distortion by means of computer simulations. Also, a numerical example is provided.
Keywords: Reversible watermarking; Recursive histogram modification; Reversible video watermarking; DIGITAL WATERMARKING; ERROR EXPANSION; IMAGE